Knowledge of the Musical Context of Yao Wedding Music in Jinxiu, Guangxi, China - Huang Xiaohuan; Arsenio Nicolas; Warakorn Seeyo (Journal of Educational Issues, 2024)
This study focused on the musical context and characteristics of Yao wedding music in Jinxiu, Guangxi, China, to use a qualitative research methodology. The objective was to 1) examine the musical context of Yao’s wedding music. 2) Analyze the musical elements of the Yao wedding music. The research designed the interview and observation forms that were used throughout the interviews and observations. By key informant, the interviews were divided into three groups. The results of the study are as follows: 1) Jinxiu Yao wedding music is related with the culture, religion, language, and history of the nation. While preserving its traditional culture, it has important national cultural significance. 2) The music of Jinxiu Yao has the most intricate musical characteristics and is performed alone or in a group with percussion instruments. With the main melody in pentatonic mode and played in a flexible rhythm, the relatively fixed wedding music is simple and simple to understand. The music and ritual of the Jinxiu Yao wedding are complementary, representing the Yao’s traditional culture and preserving the transmission of music from their ancestors through the ceremony.